2019
DOI: 10.1016/j.compchemeng.2019.106556
|View full text |Cite
|
Sign up to set email alerts
|

Computer-aided design of ionic liquids for hybrid process schemes

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…As mentioned above, the third decomposition method is used as it can significantly increase the number of cation− anion combinations and consequently enlarge the design space and the flexibility of the CAILD problem. 15,42,48 Numerous experimental data at a range of temperature of 283.15−384.15 K and pressure of 0.05−973 bar 49−66 are collected for the regression of α nm and α mn by minimizing the average absolute relative deviation (AARD, %) between experimental and calculated activity coefficients, as shown in eq 3. In this regression, additional generated pseudo-experimental data at a range of temperature of 298.15−343.15 K and 1 bar from the COSMO-RS model are also included due to the insufficient experimental data available for some IL group−gas systems.…”
Section: Il Screeningmentioning
confidence: 99%
“…As mentioned above, the third decomposition method is used as it can significantly increase the number of cation− anion combinations and consequently enlarge the design space and the flexibility of the CAILD problem. 15,42,48 Numerous experimental data at a range of temperature of 283.15−384.15 K and pressure of 0.05−973 bar 49−66 are collected for the regression of α nm and α mn by minimizing the average absolute relative deviation (AARD, %) between experimental and calculated activity coefficients, as shown in eq 3. In this regression, additional generated pseudo-experimental data at a range of temperature of 298.15−343.15 K and 1 bar from the COSMO-RS model are also included due to the insufficient experimental data available for some IL group−gas systems.…”
Section: Il Screeningmentioning
confidence: 99%
“…Computer-aided design methods have been developed and successfully applied for both organic solvent design [10][11][12][13] and IL solvent design. [14][15][16][17] For computer-aided ionic liquid design (CAILD), an IL molecule is decomposed into different structural groups and its properties are calculated using quantitative structure-property relationship models (e.g., group contribution models). With these, the IL molecular structure is optimized to achieve desired properties through the formulation and solution of a mixed-integer optimization problem.…”
Section: Introductionmentioning
confidence: 99%
“…Computer‐aided design methods have been developed and successfully applied for both organic solvent design 10–13 and IL solvent design 14–17 . For computer‐aided ionic liquid design (CAILD), an IL molecule is decomposed into different structural groups and its properties are calculated using quantitative structure–property relationship models (e.g., group contribution models).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, they have been considered as potential alternatives to volatile organic solvents in many separation processes including gas separation, [2][3][4][5] extractive distillation [5][6][7][8][9][10] and liquid-liquid extraction. [11][12][13][14][15] In the past few decades, various ILs with different functions have been synthesized by combining different cations and anions. It has been found that some ILs have very distinct solvation capacities for different gases, indicating the high-potential of using ILs as solvents in gas separations.…”
Section: Introductionmentioning
confidence: 99%